1994
DOI: 10.1111/j.1399-0004.1994.tb04161.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinical analyses of cystic fibrosis in the South of Spain

Abstract: We report molecular and clinical analyses in 71 unrelated patients with cystic fibrosis (CF) from Andalusia (South of Spain). Direct mutation analysis of six mutations of the CFTR gene (ΔF508, G542X, R1162X, N1303K, W1182X and 1949del84) was performed. The proportion of CF chromosomes with the above‐mentioned mutations was 58.5%. Haplotype analysis was performed with the marker/enzyme pairs XV2C/TaqI and KM19/PstI. A particular haplotype has been found associated with each of the studied mutations, while the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Previous studies in Spain reported specific geographic distributions for some common mutations. The p.F508del mutation showed frequencies ranging from 86% (North) to 46% (South) in the Iberian Peninsula (Casals et al 1992; Coto et al 1994; Borrego et al 1994; Telleria et al 1999) as well as a 14% prevalence of the p.G542X mutation in the Mediterranean Coastal area (Casals et al 1993). We have now found that the relative allelic frequency of this latter mutation in the Balearic Islands is 10.5% of alleles, supporting our previous estimates (Casals et al 1993; Estivill et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in Spain reported specific geographic distributions for some common mutations. The p.F508del mutation showed frequencies ranging from 86% (North) to 46% (South) in the Iberian Peninsula (Casals et al 1992; Coto et al 1994; Borrego et al 1994; Telleria et al 1999) as well as a 14% prevalence of the p.G542X mutation in the Mediterranean Coastal area (Casals et al 1993). We have now found that the relative allelic frequency of this latter mutation in the Balearic Islands is 10.5% of alleles, supporting our previous estimates (Casals et al 1993; Estivill et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports on the analysis of CFTR in Spanish CF patients have shown detection rates ranging from 58% to 90% (Borrego et al 1994; Coto et al 1994; Casals et al 1997; Telleria et al 1999), with a relatively large number of mutations remaining undetected. Herein we present the molecular analysis of 977 Spanish CF families recruited from 1988 to early 2005.…”
Section: Introductionmentioning
confidence: 97%